HUBUNGAN LATIHAN PUSH UP DAN PULL UP TERHADAP PUKULAN SMASH PADA CABANG OLAHRAGA BULUTANGKIS DI KAMPUS UNIVERSITAS MUHAMMADIYAH BONE - Al. Muh Fajri; Maria Herlinda Dos Santos; A. Ogo Darminto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between push-up and pull-up exercises and the improvement of smash stroke ability in badminton at Muhammadiyah University of Bone. The smash is a stroke technique that requires upper body muscle strength, particularly the chest, shoulders, arms, and back muscles. Push-up and pull-up exercises are believed to strengthen these muscles, thereby positively affecting smash performance.This study employed a quantitative approach using a quasi-experimental method. The research sample consisted of 20 students, divided into two groups: an experimental group that received push-up and pull-up training for six weeks, and a control group that did not receive any specific treatment. Data collection instruments included physical fitness tests and smash ability tests.The results of data analysis using paired sample t-tests and independent sample t-tests indicated a significant improvement in smash stroke ability in the experimental group compared to the control group. Therefore, push-up and pull-up exercises are proven to have a significant relationship with the improvement of smash performance in badminton. This study recommends the implementation of these exercises in regular training programs to enhance badminton playing techniques.